Transarterial chemoembolization versus hepatic resection in hepatocellular carcinoma treatment: a meta-analysis - Tian X; Dai Y; Wang D; Zhang L; Sui C; Meng F; Jiang S; Liu Y; Jiang Y (Dove Medical Press, 2015)
Xin Tian,1 Ying Dai,1 Da-qing Wang,2 Li Zhang,1 Cheng-guang Sui,1 Fan-dong Meng,1 Shen-yi Jiang,1 Yun-peng Liu,1 You-hong Jiang1 1Molecular Oncology Laboratory of Cancer Research Institute, The First Affiliated Hospital of China Medical University, Shenyang, 2Health and Family Planning Commission of Liaoning Province, People’s Republic of China Background: A number of cohort studies have compared the outcomes of transarterial chemoembolization (TACE) and hepatic resection (HR) in the treatment of hepatocellular carcinoma (HCC). However, the effect of TACE versus HR remains controversial. Therefore, we conducted a meta-analysis to assess the effectiveness of TACE and HR in HCC treatment.Materials and methods: PubMed, Embase, Web of Science, Scopus, ClinicalTrials.gov, and Cochrane library were searched from their inception until February 27, 2015 for relevant studies. The literature search was updated on May 25, 2015. Eligible studies were cohort studies comparing the survival outcomes between HCC patients undergoing TACE and HR. The primary outcome was overall survival (OS). Secondary outcomes were the recurrence rate and prognostic factors for OS. The risk ratio (RR) was used for the meta-analysis and was expressed with 95% confidence intervals (CIs).Results: This meta-analysis included eleven cohort studies with 6,297 patients, all treated with TACE or HR. Pooled estimates showed that, compared with TACE, HR significantly improved the 3-year OS (RR =0.77; 95% CI, 0.63–0.93; P=0.009). TACE and HR had similar effects on OS after 1 year (RR =0.94; 95% CI, 0.86–1.01; P=0.103), 2 years (RR =0.50; 95% CI, 0.21–1.19; P=0.114), 4 years (RR =0.61; 95% CI, 0.58–1.10; P=0.174), and 5 years (RR =0.77; 95% CI, 0.59–1.01; P=0.06). There was no significant difference between the 3-year (RR =1.31; 95% CI, 0.65–2.64; P=0.457) and 5-year recurrence rates (RR =1.14; 95% CI, 0.69–1.89; P=0.597) in the TACE and HR groups. Age (>65 vs ≤65 years; hazard ratio =0.99; 95% CI, 0.98–1.00; P=0.000), sex (male vs female; hazard ratio =0.79; 95% CI, 0.65–0.96; P=0.02), treatment method (TACE vs HR; hazard ratio =1.90; 95% CI, 1.46–2.46; P=0.000), and Eastern Cooperative Oncology Group performance score (≥1 vs 0; hazard ratio =1.69; 95% CI, 1.22–2.33; P=0.002) were independent predictors for OS.Conclusion: This meta-analysis suggests that the TACE and HR likely have similar effects in the treatment of HCC patients in terms of OS and recurrence rate. However, this conclusion should be interpreted cautiously due to the presence of further subgroup analyses with respect to outcomes in patients with different liver statuses (Barcelona Clinic Liver Cancer stage A or stage B). Keywords: transarterial chemoembolization, hepatic resection, hepatocellular carcinoma, meta-analysis